2017
DOI: 10.5455/njppp.2018.8.0729230082017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, height, gender on median and ulnar nerve conduction study

Abstract: Background: Nerve conduction studies (NCSs) is a test to measure the electrical activity in the nerve and used to measure nerve function disease progression. Physiological factors such as age, temperature, height, and gender are known to affect the nerve conduction velocity (NCV). Studies have reported different results with regard to these physiological factors affecting NCS. Aims and Objectives: To examine the influence of age, height, and gender on median and ulnar NCS. Materials and Methods: 103 healthy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Awang et al [6] also found only the decrease in CV CMAP median nerve and excluded the influence of age on CV CMAP ulnar nerve. Such results were confirmed by the studies [21,26]. Ultrasound imaging found morphological changes in the cross-section of the median nerve in the wrist and the ulnar nerve in the cubital fossa connected with age [27].…”
Section: Discussionsupporting
confidence: 74%
“…Awang et al [6] also found only the decrease in CV CMAP median nerve and excluded the influence of age on CV CMAP ulnar nerve. Such results were confirmed by the studies [21,26]. Ultrasound imaging found morphological changes in the cross-section of the median nerve in the wrist and the ulnar nerve in the cubital fossa connected with age [27].…”
Section: Discussionsupporting
confidence: 74%